Critical life cycle assessment of the innovative passive nZEB building concept 'be 2226' in view of net-zero carbon targets. (September 2022) - Maierhofer, Dominik; Röck, Martin; Ruschi Mendes Saade, Marcella; Hoxha, Endrit; Passer, Alexander
Abstract: Buildings constructed today need to be nearly-zero energy/emission buildings (nZEB) during operation. Amongst strategies to meet today's nZEB performance requirements are passive building concepts. However, it is unclear to which degree such concepts aid buildings to achieve net-zero carbon targets. To address this research gap, we conduct a life cycle assessment (LCA) of the passive nZEB concept '2226' based on its original prototype office building in Austria. We deploy a quantity takeoff and the measured end-energy demand to calculate the embodied and operational GHG emissions. In line with the recent draft of the building LCA standard EN15978, we split energy usage into building-integrated and non-integrated systems. Embodied GHG emissions make up about a third of the total life cycle GHG emissions (33%), and operational energy use accounts for two-thirds (67%) of the life cycle GHG emissions, considering the current Austrian energy grid mix. The contextualisation with the literature shows better performance in comparison to existing building standards, yet no reduction is achieved compared to buildings with similar nZEB ambitions. The measured end-energy analysis shows that two-thirds (68%) of the operational GHG emissions are allocated to building-integrated systems, i.e., those regulated by today's EU Energy Performance of Buildings Directive. Almost a third (30%) of the operational GHG emissions can be allocated to non-integrated systems, currently being reported as optional in the latest draft of the standard EN15978. We recommend extending the system boundary of building LCA including these end-energy uses by non-integrated systems in future building regulation and building LCA practice. Highlights: LCA of an innovative passive nZEB office building in Austria. Embodied GHG emissions from BIM-based quantity take off; operational GHG emissions from measured data. Allocation of operational GHG emissionsin distinct sub-modules B6.1, B6.2 and B6.3 30% of operational GHG emissions allocated to non-building integrated systems. Reflections on other studies and critical discussion in relation to net-zero carbon targets.